Ecomic / Hazalinda Harun … [et al.] - Harun, Hazalinda; Iskandar, Ainaa Idayu; Ismail, Shafinar; Ramly, Fariha Aiza; Othman, Rozana (Division of Research and Industry Linkages, 2017)
Economic subjects focus on the behavior and interactions of economic agents and how economies work namely microeconomics and macroeconomics. Microeconomics examines the behavior of basic elements in the economy, while, macroeconomic analyze the entire economy such as aggregated production, consumption, savings, and investment and issues affecting it. Economic subjects often perceived as a difficult and tough subjects for student because they need to understand terms and theories in both microeconomic and macroeconomic. Failing to understand the abstract concept of economic subjects will effect the student ability to relate with the real practice. With an average Malaysians spend 12 hours a day on the internet according to the Multimedia and Communications Ministry (2014), Malaysia has an active internet users surpassing 19 million users with 98% of them using social media and social media multitasking has become common to Gen-Y. In an effort to increase the student ability to understand the economic subjects, the use of social media and application (Apps) was introduced to motivate learning about economic subjects. Social media multitasking has shown it negative relationship with student performance (Lau, 2017). Thus, the objective of this research is to propose comic apps in learning and teaching economic subjects by using bitstrips application as a tool because it is a free and friendly to use apps. The outcome of the innovation is ‘eco-mic’, an interactive approach to explain and deliver the concept of economic using comic style to assist student to learn economic subjects and lecturer to deliver economic knowledge in classroom.